Agricultural Economics as a Poster Child of Applied Economics: Big Data & Big Issues. (10th January 2019) - Zilberman, David
Abstract: Agricultural economists have embodied the notions of applied economics for a long time. They have used economic principles to address real-world problems, integrating economics and scientific knowledge. Applied economics tends to be multidisciplinary and develop applied concepts, theories, and tools. Some, like human capital, diffusion of innovation, contingent valuation, and numerous numerical and econometric techniques have spread throughout economics. Agricultural economic research has been data intensive, and improved information technologies strengthen this tendency. Yet data without theory is of limited use and coevolution of theory and data are essential. Empirical analysis should incorporate quantitative information as well as narratives. We are challenged to understand the coevolution of business, supply chains, and technology, and how they are affected by policies and affect markets. Research should integrate agriculture, energy, and the environment and develop tools to analyze and regulate the emerging bio-economy integrating biotech and infotech.